Institutional constraints and regional incentives for the attempt to scrap presidential term limits. Issue 4 (19th May 2022) - Lofty, Dina Osama
ABSTRACT: Following the current debate on the existence of a third wave of autocratization, this article focuses on one of the most prominent features of democratic recession and deepening autocratization which is scrapping presidential terms. I argue that it is important to consider formal institutions while studying the decision to scrap term limits, and not only the outcome. Based on a 289 presidential/semi presidential sample, starting from the third wave till 2020, the findings, using logistic regression models, indicate that the higher the institutional constraints are, the less likely the president is to attempt scrapping term limits. Moreover, the president decides to extend more than to abolish or avoid term limits when there are higher institutional constraints. Furthermore, this article argues that regional partners/presidents who attempt to change term limits motivate other presidents to do the same. The results show that precedent regional and sub-regional attempts positively affect the president's decision to attempt to change term limits. Moreover, security challenges in the region are used as a pretext for staying longer in office, for it is argued that if the president leaves his/her rule, the country will face a breakdown and the whole region will be affected.